Non-Chemical Control of Charcoal Rot of Urdbean by Sonchus oleraceous Application - BANARAS,S. (2020)
ABSTRACT: Urdbean [Vigna mungo (L.) Hepper] is an important leguminous crop whose production is severely affected by charcoal rot disease caused by Macrophomina phaseolina. This study was undertaken to seek an environmental friendly alternative to synthetic fungicides for management of this disease. Dry biomass of an allelopathic weed Sonchus oleraceous L. was used to combat the menace. Fumigated sandy loam pot soil, pre-inoculated with M. phaseolina, was amended with different doses of dry biomass of the weed ranging from 0.5% to 3%. Application of 2% weed biomass completely controlled the disease. Soil inoculation with M. phaseolina inoculation (positive control) reduced shoot dry weight and grain yield of urdbean by 59% and 91%, respectively, over negative control. Application of different doses of soil amendment in pathogen inoculated soil enhanced shoot dry weight and grain yield of urdbean by 107-307% and 438-7400%, respectively, over positive control. The highest positive effect on growth and yield of uedbean in M. phaseolina contaminated soil was recorded due to 2.5% amendment. M. phaseolina inoculation significantly enhanced peroxidase (POX) and phenyl alanine ammonia lyase (PAL) activities. However, application of different doses of S. oleraceous biomass to the soil gradually decreased activities of these enzymes. The present study concludes that application of 2.5% dry biomass of S. oleraceous can completely control charcoal rot of urdbean and significantly enhance crop growth and yield.